Theology as a vocation : Ernst Troeltsch as philosophical theologian - Chapman, M (1988)
This thesis attempts a systematisation of Troeltsch's work which takes as its starting point the distinctive philosophical and theological problems arising from the modern conditions of humanity and society. These centre on the fundamental conflict of autonomy and the need for authority - the impasse of the Enlightenment. The theologian's vocation is to attempt to re-integrate the individual within absolute structures of authority without denying the individual's autonomy. Troeltsch 1 s project is seen as in some ways anticipating that of Maclntyre in After Virtue. Troeltsch does not attempt to recreate the medieval synthesis, nor to isolate Christianity from the world, but to combine the relative structures of the modern world with the absolute structures of authority embodied in Christianity. The basis for Troeltsch's solution rests upon his philosophy of religion, which owes its distinctive character to Kant and the critical idealism deriving from him. Troeltsch moves beyond Kant, however, in his notion of the interpenetration of the spheres of practical and theoretical reason. This interpenetration alone allows for the survival of the autonomy of the individual. The attempt to grasp reality sub specie aeternitatis, the a priori of religion, is restricted by human finitude. This finitude determines the shape of Troeltsch's systematic theology, which rests upon the relation of the human will to the divine will, of the relative to the absolute. It is the responsibility of human beings to attempt to progress towards the absolute, to adopt the divine will, even in the knowledge that this can never be fully achieved. Faith and hope are realised in ethical activity. The realisation of the absolute is the creation of the most universal context for ethical action, whereby each individual might reshape reality unfettered by all finite claims on absoluteness, and thereby be united with divine creativity itself.